Patient and healthcare delays in critical and non-critical pulmonary tuberculosis incidence areas in Portugal: are there differences?. (December 2021) - Almeida Santos, J.; Soares, P.; Leite, A.; Duarte, R.; Nunes, C.
Abstract: Objectives: To characterize patient, healthcare, and total delay in diagnosing pulmonary tuberculosis (PTB) in critical (higher PTB incidence) and non-critical (lower PTB incidence) areas and their determinants considering clinical and sociodemographic factors. Study design: Retrospective cohort study. Methods: Data was retrieved from the Portuguese National Tuberculosis Surveillance System (SVIG-TB). Were included in the study all active PTB patients ( n = 11, 762) notified between 2008 and 2017. Spatial analysis was used to define critical and non-critical areas. Kaplan–Meier estimator, logrank test, and Cox regression were conducted, stratified by area. Results: PTB cases in critical areas ( n = 6594, 56.1%) presented longer patient median delay (41 vs 31days), shorter healthcare median delay (7 vs 10 days), and longer total median delay (63 vs 61days) t.han non-critical areas. Patient and total delay increased in both areas over time, while healthcare delay only increased in non-critical areas. Icn both areas, being from a high TB incidence country and alcohol abuse were associated with longer patient delays. Being female, older age, and oncologic diseases were associated with longer healthcare delays. Respiratory diseases were only associated with a longer healthcare delay in non-critical areas. Being female, older, and from a high TB incidence country were associated with a longer total delay in both areas. Conclusions: Patient delay was significantly longer in critical areas, and healthcare delay was significantly longer in non-critical areas. Several factors associated with longer delays have been identified, most of which are shared by critical and non-critical areas. Differences in patient and healthcare delay, for example, by sex, age, or country of birth, highlight the need for targeted public health interventions to help reduce these differences.